Bench Mark Survey Report on Morsi Block Bombay - Planning Commission (Planning Commission, 1956)
Among the objectives of evaluation work undertaken by the Programme Evaluation Organisation, two of the more important are—(i) assessment of the extent of adoption of improved practices advocated by the community development and national extension service programmes and (ii) obtaining insight into the impact of these programmes upon the economic and social life of the rural people.
Planning Commission Programme Evaluation Organisation Government of India